Environmental impacts of trypanosomiasis control through land-use change: Conceptual model, approach and preliminary results - Reid, Robin S.; Kruska, Russell L.; Ellis, J.E.; Wilson, C.J.; Perry, Brian D. (OAU/STRC, 1995)
More effective control of tsetse-transmitted trypanosomiasis may open vast areas of Africa to livestock production, both increasing food production and endangering biodiversity on the continent. This paper Reports on the Development of a conceptual model of the linkages between trypanosomiasis control and land-use, and then discusses approaches to determine how land-use change affects the environment. The conceptual model integrates epidemiological, ecological, economic and social information into the study of control-induced changes in land-use at continental, regional, national and local scales. Geographical information systems (GIS) are used to generate hypotheses and to analyse broad-scale patterns, while field studies are used to establish causality and to ground-truth large-scale data sets. Preliminary analyses provide support for the hypothesis that trypanosomiasis is retarding the large-scale correlations show that there is no simple inverse relationship between the presence of tsetse and the presence of agricultural land-use and that tsetse appears to limit agricultural land-use more strongly in southern than in West Africa. These results imply that decisions concerning where and when to control trypanosomiasis can have strong implications for the success of efforts to enhance human welfare and to maintain environmental quality.